APPROACHES TO CHOOSING A METHOD OF RESTORATION OF AUXILIARY TEETH IN PROSTHETICS WITH REMOVABLE PARTIAL DENTURES. (Journal of Multidisciplinary Sciences and Innovations, 2025)
Summary Different methods of teeth restorations at the treatment of dentition defects with the help of different partial removable dentures are considered in this article. The use of thermoplastic clasps is concluded to be the most optimal one for direct composite restorations of supporting teeth hard tissues.